Assistive Technologies and Academic Engagement: Evidence from Mainstream Inclusive Schools - Yadav, Mukesh Kumar; Singh, Anurag; Verma, Nancy; Kushwaha, Ravindra Kumar (CV. Rayyan Dwi Bharata, 2026)
The present study investigates the impact of assistive technologies (ATs) on academic engagement among students with disabilities in mainstream inclusive schools. Recognizing the increasing adoption of ATs as tools to enhance accessibility and participation, this research examines how these technologies influence behavioural, cognitive, and emotional engagement, alongside the role of institutional and pedagogical support. A quantitative descriptive–correlational design was employed, involving a sample of 35 students with diverse disabilities and five special subject teachers from inclusive schools in Kota. Data were collected using validated instruments, including an Assistive Technology Utilization Scale, a Student Academic Engagement Scale, and a Teacher Questionnaire. Descriptive analysis indicated moderate to high overall academic engagement, with cognitive engagement being the highest (M = 3.85). Correlation analysis revealed significant positive relationships between AT use and behavioural (r = .52, p .01), cognitive (r = .58, p .01), and emotional engagement (r = .46, p .05). Independent samples t-tests demonstrated that students who regularly used ATs exhibited significantly higher engagement than those with limited use. Multiple regression analysis further identified AT use (β = .49, p .01) and teacher training (β = .32, p .05) as significant predictors of academic engagement, highlighting the importance of supportive institutional environments. Findings suggest that ATs serve not only as access tools but also as facilitators of meaningful learning, autonomy, and social participation. The study underscores the need for strategic integration of ATs, teacher professional development, and institutional support to foster equitable and effective inclusive education.